Entrepreneurship frameworks and empirical investigations from forthcoming leaders of European research - Wiklund, Johan (Advances in entrepreneurship, firm emergence and growth ;, 2006)
Among the major ways researchers think about research topics and approaches, the lesson of these ten chapters by many of the new breed of European entrepreneurship researchers is that those values and world-views which have traditionally been the hallmark of the European approach, remain evident as the underpinnings of the new breed approach. In doing so, the field of entrepreneurship will grow in terms of the range of ideas, data sources, and techniques. It will also grow more competitive, initially through the addition of new people, but as their ideas begin to gain traction, as differing worldviews and approaches come to the fore, and perhaps sometimes into conflict. However, that sort of exchange, one which broadens each participant, is what science and academia is all about, and the new breed, through efforts such as the volume you are holding, are working to initiate that process. This title highlights 'new breed' thinking and focuses on European entrepreneurship. This book series is available electronically at website.